Cherry pit-derived magnetic porous carbon-based composite wave-absorbing material as well as preparation method and application thereof

By synthesizing magnetic porous carbon-based composite absorbing materials using raw materials such as cherry pits and FeCl3, the existing absorbing materials have been solved, and the effects of low-cost, simple preparation and wide-band absorption performance have been achieved.

CN119703104APending Publication Date: 2025-03-28LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411742608.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Existing absorbing materials have limitations such as high cost, complex preparation process, and narrow absorption frequency range, which are difficult to meet practical application requirements.

Method used

The cherry pit was used as the carbon source, combined with FeCl3 and heteroatom dopants, and a cherry pit-derived magnetic porous carbon-based composite absorbing material was synthesized by one-step pyrolysis method. This material enhances the attenuation ability of electromagnetic waves through the synergistic effect of magnetic loss, dielectric loss and impedance matching.

Benefits of technology

Composite absorbing materials with low cost, simple preparation and wide-band absorption performance are suitable for industrial production and show great potential in areas such as military stealth.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119703104A_ABST
    Figure CN119703104A_ABST
Patent Text Reader

Abstract

The invention provides a cherry pit-derived magnetic porous carbon-based composite wave-absorbing material and a preparation method and application thereof.The preparation method comprises the steps that FeCl3, cherry pit powder and a heteroatom doping agent are dispersed in absolute ethyl alcohol in a stirring state, stirring continues till ethyl alcohol is completely volatilized, and a solid mixture is obtained; grinding the solid mixture to obtain a precursor mixture; and placing the precursor mixture in a tubular furnace, and calcining in an inert gas atmosphere to obtain the composite wave-absorbing material. The composite wave-absorbing material is applied to the field of microwave absorption. According to the cherry pit derived magnetic porous carbon-based composite wave-absorbing material provided by the invention, single loss is changed into a composite wave-absorbing material with multiple electromagnetic loss mechanisms, that is, the wave-absorbing performance of the composite wave-absorbing material is improved through the synergistic effect of magnetic loss, dielectric loss and enhanced impedance matching.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of microwave absorbing materials, and in particular to a cherry pit-derived magnetic porous carbon-based composite absorbing material and a preparation method and application thereof. Background Art

[0002] The proliferation of modern electronic devices has led to an increasingly prominent problem of electromagnetic radiation pollution. The research and utilization of electromagnetic wave absorbing materials have attracted great attention in the field of materials science. Absorbing materials can effectively convert microwave energy into heat and other energy through mechanisms such as polarization, resonance and conduction, and dissipate it. This is a very effective solution to problems related to electromagnetic pollution and interference, and shows great application potential in the fields of military stealth technology, electromagnetic shielding and electromagnetic pollution control. In general, absorbing materials are divided into dielectric materials, such as graphene, carbon nanotubes and conductive polymers, and magnetic materials, including Mn / Fe / Co / Ni-based materials, ferrites and alloys. Dielectric materials usually reduce microwave energy through dipole polarization relaxation or microcurrent mechanisms, while magnetic materials achieve this goal by utilizing eddy current losses and natural resonance.

[0003] However, traditional absorbers, such as metals, magnetic oxides, and ceramics, often have limitations such as high cost, complex preparation process, and narrow absorption frequency range, which are difficult to meet the requirements of practical applications. Therefore, the development of efficient, low-cost, broadband absorbers has become an important research topic in current materials science.

[0004] Low-dimensional carbon materials, including graphene, carbon nanotubes (CNTs), carbon nanofibers (CNFs), and nanoporous carbon (NPCs), show good potential in electromagnetic shielding due to their low cost, low density, and suitable conductivity. At the same time, biomass-derived renewable and sustainable carbon materials have attracted increasing attention in the field of wave absorption due to their natural properties. However, most carbon-based composites have limited absorption bandwidth due to high reflectivity and insufficient impedance matching. Summary of the invention

[0005] The present application provides a cherry pit-derived magnetic porous carbon-based composite absorbing material and a preparation method and application thereof, in order to solve the above-mentioned problems mentioned in the background technology.

[0006] The present application provides a method for preparing a cherry pit-derived magnetic porous carbon-based composite absorbing material, the preparation method comprising:

[0007] (1) dispersing FeCl3, cherry pit powder and heteroatom dopant in anhydrous ethanol under stirring, and continuing to stir until the ethanol is completely volatilized to obtain a solid mixture;

[0008] (2) grinding the solid mixture to obtain a precursor mixture;

[0009] (3) placing the precursor mixture in a tube furnace and calcining it in an inert gas atmosphere to obtain a composite absorbing material.

[0010] Optionally, the heteroatom dopant includes melamine or Na2S2O3·5H2O.

[0011] Optionally, the weight ratio of cherry pit powder to Fe atoms is 1:1, and the mass percentage of heteroatom dopant in the composite absorbing material is 5-20%.

[0012] Optionally, the weight volume ratio of cherry pit powder to anhydrous ethanol is 2g:25-30mL.

[0013] Optionally, in step (1), the temperature during the preparation of the solid mixture is 60-65°C.

[0014] Optionally, the particle size of the precursor mixture is 80-100 mesh.

[0015] Optionally, the calcination process specifically includes: placing the precursor mixture in a tubular furnace, heating it to 800°C at a heating rate of 5°C / min in an inert gas atmosphere, calcining it at 800°C for 6 hours, and then naturally cooling it to room temperature to obtain a composite absorbing material.

[0016] Optionally, the inert gas includes argon or nitrogen.

[0017] On the other hand, the present application provides a cherry pit-derived magnetic porous carbon-based composite absorbing material, which is made by the above-mentioned preparation method.

[0018] On the other hand, the present application provides an application of a cherry pit-derived magnetic porous carbon-based composite absorbing material, the composite absorbing material is made by the above method, or is the above composite absorbing material, and the composite absorbing material is applied in the field of microwave absorption.

[0019] The cherry pit-derived magnetic porous carbon-based composite absorbing material and its preparation method and application provided in the present application realize the preparation and application of the cherry pit-derived magnetic porous carbon-based composite absorbing material, and compared with the prior art, it has the following beneficial effects:

[0020] (1) A composite absorbing material was synthesized by a one-pot sintering method using anhydrous FeCl3, heteroatom dopants and cherry pit powder as precursors. During the calcination process, a porous carbon material was formed while iron nanoparticles and heteroatoms were firmly attached to the porous structure of the carbon material. The porous carbon material, iron nanoparticles and heteroatoms synergistically acted through magnetic loss, dielectric loss and enhanced impedance matching, which helped to enhance the attenuation of electromagnetic waves by the composite absorbing material.

[0021] (2) The composite absorbing material FeN provided in this application 0.1 -BC has an effective absorption bandwidth of 4.8GHz at 1.5mm, and a minimum reflection loss of -63.2dB. This is due to the co-doping of iron and heteroatoms into the biochar composite material. First, the magnetic nanoparticles are firmly adsorbed on the surface of the conductive carbon substrate to form a "microcapacitor" structure, which intensifies the interface polarization, leading to charge accumulation and uneven distribution, thereby generating a new electromagnetic field and further enhancing the absorption capacity. In addition, the carbon material treated with high-temperature pyrolysis has inherent defects and functional groups, which are conducive to the induction of defect polarization, resulting in an increase in dipole polarization loss. At the same time, polarization induction strengthens electron transfer and generates heat energy, consuming electromagnetic waves. Moreover, the three-dimensional porous carbon in the composite absorbing material can provide a conductive path for electron migration and jumping, thereby introducing conductive losses, thereby attenuating the incident electromagnetic waves.

[0022] (3) The present application adopts cherry pits as a carbon source, which not only realizes the preparation of absorbing materials, but also recycles biomass waste. The raw materials are widely available, renewable, cheap and easy to obtain, while reducing the preparation cost of composite absorbing materials.

[0023] (4) The preparation process of the present application is simple, the doping type and quality of heteroatoms can be precisely controlled, and the synthesis cost is low. No complex synthesis equipment and chemical reagents are required, which is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, a brief introduction will be given below to the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0025] Figure 1 A preparation process diagram of a composite absorbing material provided in one embodiment of the present application;

[0026] Figure 2 Raman characterization diagram of the composite absorbing material provided in Examples 1 to 3, Example 5 and Comparative Example 1 of the present application;

[0027] Figure 3 XPS graph of the composite absorbing material provided in Example 2, Example 5 and Comparative Example 1 of the present application;

[0028] Figure 4 This is a morphology characterization diagram of the composite absorbing material provided in Examples 2 and 5 of the present application. Figure 4 (a) is a SEM image of the composite absorbing material obtained in Example 5. Figure 4(b) is a SEM image of the composite absorbing material obtained in Example 2. Figure 4 (c) is a TEM image of the composite absorbing material obtained in Example 2;

[0029] Figure 5 2D and 3D reflection loss contour diagrams of the composite absorbing materials provided in Example 2, Example 5 and Comparative Example 1 of the present application, Figure 5 (a) is the 2D reflection loss contour diagram of comparative example 1, Figure 5 (b) is a 3D reflection loss contour diagram of Comparative Example 1; Figure 5 (c) is a 2D reflection loss contour diagram of Example 2, Figure 5 (d) is a 3D reflection loss contour map of Example 2; Figure 5 (e) is a 2D reflection loss contour diagram of Example 5, Figure 5 (f) is a 3D reflection loss contour map of Example 5;

[0030] Figure 6 2D and 3D reflection loss contour diagrams of Examples 1 to 3 of the present application, Figure 6 (a) is a 2D reflection loss contour diagram of Example 1, Figure 6 (b) is a 3D reflection loss contour map of Example 1; Figure 6 (c) is a 2D reflection loss contour diagram of Example 2, Figure 6 (d) is a 3D reflection loss contour map of Example 2; Figure 6 (e) is a 2D reflection loss contour diagram of Example 3, Figure 6 (f) is a 3D reflection loss contour map of Example 3;

[0031] Figure 7 Graphs showing reflection loss (RL) and frequency (f) of the composite material of Example 2 with different thicknesses. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application is clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work also fall within the scope of protection of the present application.

[0033] like Figure 1 As shown, the present application provides a method for preparing a cherry pit-derived magnetic porous carbon-based composite absorbing material, the preparation method comprising:

[0034] (1) dispersing FeCl3, cherry pit powder and heteroatom dopant in anhydrous ethanol under stirring, and continuing to stir until the ethanol is completely volatilized to obtain a solid mixture;

[0035] (2) grinding the solid mixture to obtain a precursor mixture;

[0036] (3) placing the precursor mixture in a tube furnace and calcining it in an inert gas atmosphere to obtain a composite absorbing material.

[0037] Specifically, in the preparation process of the composite absorbing material provided by the present application, cherry pits are used as a carbon source, FeCl3 is used as a magnetic material iron, and a heteroatom dopant is used as a heteroatom to synthesize an iron and heteroatom co-doped biochar composite material by a one-step pyrolysis method. Before the reaction, the cherry pits are ground and filtered with a 100-mesh screen to obtain cherry pit powder, which is used in subsequent reactions.

[0038] Disperse FeCl3, cherry pit powder and heteroatom dopant in anhydrous ethanol and stir to make the raw materials evenly mixed, which is beneficial to improve the subsequent reaction efficiency. After the raw materials are dispersed, continue to stir until the ethanol is completely volatilized to obtain a solid mixture. Anhydrous ethanol is not only used as a dispersion medium, which is beneficial to the full mixing of the raw materials, but also easy to volatilize, easy to operate, and inexpensive, environmentally friendly and non-toxic. Grind the solid mixture with a mortar to make the particle size of the solid mixture smaller and more uniform, which is beneficial to the formation of porous carbon materials in the subsequent calcination process. At the same time, the iron nanoparticles and heteroatoms are evenly and firmly attached to the porous structure of the carbon material. The porous carbon material, iron nanoparticles and heteroatoms work synergistically to improve the absorbing performance of the composite absorbing material. The prepared composite absorbing material is named: FeX n -BC, where BC represents biomass carbon, X represents a heteroatom, and X n The subscripts in represent the mass ratio of the heteroatom dopant.

[0039] The present application does not limit the stirring method and stirring speed, and the stirring method commonly used in the art can be used to achieve the effect of uniformly dispersing the raw materials.

[0040] The carbon source of the composite absorbing material of the present application can also come from plant roots, stems, branches, leaves, fruits and flowers, etc., more preferably, from plant residues such as grape residues and walnut shells. The heteroatom can also be selected from boron, phosphorus and the like.

[0041] Cherry pits are calcined and carbonized to obtain a carbon material with a three-dimensional porous layered structure, so that the composite absorbing material has better conductivity, helps to attenuate electromagnetic waves, improves impedance matching characteristics, and makes it easier for electromagnetic waves to enter the material and be absorbed. The introduction of heteroatoms in the carbon structure can produce defects and dipoles, which is conducive to the enhancement of polarization loss; the presence of a single pair of electrons in the heteroatom dopant enhances the mobility of electrons, promotes conduction losses, and thus improves dielectric losses. At the same time, after calcination, spherical iron nanoparticles are attached to the porous carbon, combining the carbon material with magnetic particles to balance impedance matching, enhance absorption intensity, and broaden the absorption bandwidth. The presence of ferromagnetic components can cause magnetic losses, and the complementarity between magnetic components and dielectric components can be balanced. Therefore, the composite absorbing material provided by the present application has multiple electromagnetic loss mechanisms, namely the synergistic effect of magnetic loss, dielectric loss, and enhanced impedance matching.

[0042] The present application realizes the preparation of composite absorbing materials through the above scheme, and synthesizes the composite absorbing materials by a one-pot sintering method using anhydrous FeCl3, heteroatom dopants and cherry pit powder as precursors. While forming a porous carbon material during the calcination process, the iron nanoparticles and heteroatoms are firmly attached to the porous structure of the carbon material. The porous carbon material, the iron nanoparticles and the heteroatoms help to enhance the attenuation of electromagnetic waves by the composite absorbing material through the synergistic effect of magnetic loss, dielectric loss and enhanced impedance matching.

[0043] Optionally, the heteroatom dopant includes melamine or Na2S2O3·5H2O.

[0044] Specifically, by doping heteroatoms N or S, since heteroatoms have higher electronegativity than C atoms, they can attract surrounding electrons, resulting in charge redistribution between N or S and C atoms. This charge transfer increases the concentration of free electrons in the material, thereby improving its conductivity. It helps to guide the composite material to convert electromagnetic wave energy into heat energy and enhance the attenuation of electromagnetic waves. Heteroatom doping introduces more heterogeneous interfaces (such as NC and N-Fe interfaces) into the material. These interfaces produce interfacial polarization effects under electromagnetic wave irradiation, enhancing the material's wave absorption performance.

[0045] Optionally, the weight ratio of cherry pit powder to Fe atoms is 1:1, and the mass percentage of heteroatom dopant in the composite absorbing material is 5-20%.

[0046] Specifically, the weight ratio of cherry pit powder to Fe atoms is controlled. After carbonization, iron nanoparticles and heteroatoms are attached to the porous structure of the carbon material. Excessive Fe atoms will cause the agglomeration of iron nanoparticles, and will not further promote the absorbing performance of the composite absorbing material.

[0047] At the same time, by changing the amount of heteroatom dopant added, the heteroatom doping level can be adjusted. Insufficient heteroatom doping has a not-so-significant effect on changing the electromagnetic properties of biochar, while excessive heteroatom doping will destroy the material structure, excessively increase the conductivity, or disrupt the polarization mechanism, while leading to the introduction of too many defects and scattering centers, hindering electron transfer or reducing the electromagnetic wave scattering efficiency, and ultimately reducing its attenuation effect on electromagnetic waves.

[0048] The different mass percentages of heteroatom dopants in the composite absorbing material include but are not limited to the following: FeN 0.05 -BC, FeN 0.1 -BC and FeN 0.2 -BC, wherein the subscripts 0.05, 0.1, and 0.2 indicate that the mass ratios of the heteroatom dopant are 5%, 10%, and 20%, respectively.

[0049] Optionally, the weight volume ratio of cherry pit powder to anhydrous ethanol is 2g:25-30mL.

[0050] Specifically, an appropriate amount of anhydrous ethanol helps to provide a dispersion medium for the precursor, which can satisfy the sufficient mixing of various raw materials. If the anhydrous ethanol is excessive, it fails to further promote the uniform dispersion of the raw materials, and subsequent stirring is required for the complete volatilization of the anhydrous ethanol, which reduces production efficiency and increases resource consumption.

[0051] Optionally, in step (1), the temperature during the preparation of the solid mixture is 60-65°C.

[0052] Specifically, controlling the temperature of the solid mixture during mixing is beneficial to the diffusion of molecules, improving the mixing efficiency, and further helping to improve the subsequent reaction efficiency.

[0053] Optionally, the particle size of the precursor mixture is 80-100 mesh.

[0054] Specifically, during the calcination process of the precursor mixture, the cherry pit that provides the carbon source forms a carbon material with a three-dimensional porous layered structure, so that the composite absorbing material has better conductivity, which helps to attenuate electromagnetic waves. At the same time, the specific surface area of ​​the carbon material is increased, so that the iron nanoparticles and heteroatoms are more evenly and firmly attached to the porous carbon, and then the porous carbon material, iron nanoparticles and heteroatoms work synergistically through magnetic loss, dielectric loss and enhanced impedance matching, thereby improving the composite absorbing material's loss of electromagnetic waves.

[0055] Optionally, the calcination process specifically includes: placing the precursor mixture in a tubular furnace, heating it to 800°C at a heating rate of 5°C / min in an inert gas atmosphere, calcining it at 800°C for 6 hours, and then naturally cooling it to room temperature to obtain a composite absorbing material.

[0056] Specifically, by controlling the calcination temperature and time, the graphitization degree of the composite absorbing material is controlled, so that defects exist inside the graphite carbon layer of the composite absorbing material, which is conducive to the induction of defect polarization. Defects can trigger polarization relaxation, leading to an increase in dipole polarization loss. At the same time, it can help strengthen electron transfer and generate heat energy, consuming electromagnetic waves.

[0057] Optionally, the inert gas includes argon or nitrogen to exclude oxygen.

[0058] On the other hand, the present application provides a cherry pit derived magnetic porous carbon-based composite absorbing material, which is prepared by the above-mentioned preparation method. The composite absorbing material provided by the present application has multiple electromagnetic loss mechanisms, namely, the synergistic effect of magnetic loss, dielectric loss and enhanced impedance matching.

[0059] On the other hand, the present application provides an application of a cherry pit-derived magnetic porous carbon-based composite absorbing material, the composite absorbing material is made by the above method, or is the above composite absorbing material, and the composite absorbing material is applied to the field of microwave absorption. More preferably, the composite absorbing material is applied to the military field, and the composite absorbing material is applied to the fuselage skin of a fighter jet, which can effectively prevent it from being detected by radar and achieve "stealth".

[0060] The technical solution of the present application is described in detail below with reference to specific embodiments.

[0061] Example 1

[0062] A method for preparing a cherry pit-derived magnetic porous carbon-based composite wave-absorbing material, the method comprising:

[0063] (1) Grind the cherry pits and filter them with a 100-mesh sieve to obtain cherry pit powder. Take 5.78 g of FeCl3, 2.0 g of cherry pit powder and 0.2 g of melamine, stir and disperse them in 25 mL of anhydrous ethanol at a temperature of 60°C, and continue stirring until the ethanol is completely volatilized to obtain a solid mixture;

[0064] (2) grinding the solid mixture to obtain a precursor mixture with a particle size of 80-100 mesh;

[0065] (3) The precursor mixture was placed in a tube furnace, heated to 800°C at a heating rate of 5°C / min in an argon atmosphere, calcined at 800°C for 6 hours, and then naturally cooled to room temperature to obtain a composite absorbing material named FeN 0.05 -BC.

[0066] Example 2

[0067] A method for preparing a cherry pit-derived magnetic porous carbon-based composite wave-absorbing material, the method comprising:

[0068] (1) Grind the cherry pits and filter them with a 100-mesh sieve to obtain cherry pit powder. Take 5.78 g of FeCl3, 2.0 g of cherry pit powder and 0.4 g of melamine, stir and disperse them in 25 mL of anhydrous ethanol at 62°C, and continue stirring until the ethanol is completely evaporated to obtain a solid mixture;

[0069] (2) grinding the solid mixture to obtain a precursor mixture with a particle size of 80-100 mesh;

[0070] (3) The precursor mixture was placed in a tube furnace, heated to 800°C at a heating rate of 5°C / min in an argon atmosphere, calcined at 800°C for 6 hours, and then naturally cooled to room temperature to obtain a composite absorbing material named FeN 0.1 -BC.

[0071] Example 3

[0072] A method for preparing a cherry pit-derived magnetic porous carbon-based composite wave-absorbing material, the method comprising:

[0073] (1) Grind the cherry pits and filter them with a 100-mesh sieve to obtain cherry pit powder. Take 5.78 g of FeCl3, 2.0 g of cherry pit powder and 0.8 g of melamine, stir and disperse them in 30 mL of anhydrous ethanol at a temperature of 65°C, and continue stirring until the ethanol is completely evaporated to obtain a solid mixture;

[0074] (2) grinding the solid mixture to obtain a precursor mixture with a particle size of 80-100 mesh;

[0075] (3) The precursor mixture was placed in a tube furnace, heated to 800°C at a heating rate of 5°C / min in an argon atmosphere, calcined at 800°C for 6 hours, and then naturally cooled to room temperature to obtain a composite absorbing material named FeN 0.2 -BC.

[0076] Example 4

[0077] A method for preparing a cherry pit-derived magnetic porous carbon-based composite wave-absorbing material, the method comprising:

[0078] (1) Grind the cherry pits and filter them with a 100-mesh sieve to obtain cherry pit powder. Take 5.78 g of FeCl3, 2.0 g of cherry pit powder and 0.3 g of Na2S2O3·5H2O, stir and disperse them in 25 mL of anhydrous ethanol at 60°C, and continue stirring until the ethanol is completely evaporated to obtain a solid mixture;

[0079] (2) grinding the solid mixture to obtain a precursor mixture with a particle size of 80-100 mesh;

[0080] (3) The precursor mixture was placed in a tube furnace, heated to 800°C at a heating rate of 5°C / min in an argon atmosphere, calcined at 800°C for 6 hours, and then naturally cooled to room temperature to obtain a composite absorbing material named FeS 0.05 -BC.

[0081] Example 5

[0082] A method for preparing a cherry pit-derived magnetic porous carbon-based composite wave-absorbing material, the method comprising:

[0083] (1) Grind the cherry pits and filter them with a 100-mesh sieve to obtain cherry pit powder. Take 5.78 g of FeCl3, 2.0 g of cherry pit powder and 0.69 g of Na2S2O3·5H2O, stir and disperse them in 25 mL of anhydrous ethanol at 62°C, and continue stirring until the ethanol is completely evaporated to obtain a solid mixture;

[0084] (2) grinding the solid mixture to obtain a precursor mixture with a particle size of 80-100 mesh;

[0085] (3) The precursor mixture was placed in a tube furnace, heated to 800°C at a heating rate of 5°C / min in an argon atmosphere, calcined at 800°C for 6 hours, and then naturally cooled to room temperature to obtain a composite absorbing material named FeS 0.1 -BC.

[0086] Example 6

[0087] A method for preparing a cherry pit-derived magnetic porous carbon-based composite wave-absorbing material, the method comprising:

[0088] (1) Grind the cherry pits and filter them with a 100-mesh sieve to obtain cherry pit powder. Take 5.78 g of FeCl3, 2.0 g of cherry pit powder and 1.6 g of Na2S2O3·5H2O, stir and disperse them in 25 mL of anhydrous ethanol at a temperature of 65°C, and continue stirring until the ethanol is completely evaporated to obtain a solid mixture;

[0089] (2) grinding the solid mixture to obtain a precursor mixture with a particle size of 80-100 mesh;

[0090] (3) The precursor mixture was placed in a tube furnace, heated to 800°C at a heating rate of 5°C / min in an argon atmosphere, calcined at 800°C for 6 hours, and then naturally cooled to room temperature to obtain a composite absorbing material named FeS 0.2 -BC.

[0091] Comparative Example 1

[0092] A method for preparing a cherry pit-derived magnetic porous carbon-based composite wave-absorbing material, the method comprising:

[0093] (1) Grind the cherry pits and filter them with a 100-mesh sieve to obtain cherry pit powder. Take 5.78 g of FeCl3 and 2.0 g of cherry pit powder, stir and disperse them in 25 mL of anhydrous ethanol at 60°C, and continue stirring until the ethanol is completely evaporated to obtain a solid mixture;

[0094] (2) grinding the solid mixture to obtain a precursor mixture with a particle size of 80-100 mesh;

[0095] (3) The precursor mixture is placed in a tube furnace, heated to 800°C at a heating rate of 5°C / min in an argon atmosphere, calcined at 800°C for 6 hours, and then naturally cooled to room temperature to obtain a composite absorbing material named Fe-BC.

[0096] Experimental Example 1

[0097] Raman Characterization Analysis of Composite Absorbing Materials

[0098] During the experiment, the applicant found that the performance of the composite absorbing material was lower when the heteroatom was S than when the heteroatom was N. Therefore, Examples 1 to 3 and Example 5 (FeS 0.1 -BC) is used as a representative to characterize and explain the characteristics and performance of the composite absorbing material.

[0099] In this experimental example, Raman characterization was performed on the composite absorbing materials provided in Examples 1 to 3, Example 5 and Comparative Example 1. The results are as follows: Figure 2 shown.

[0100] observe Figure 2 It can be seen that at 1340cm -1 and 1580cm -1 There are two obvious prominent bands at the two ends. These bands correspond precisely to the established D and G bands, which are characteristic marks of carbon materials. The D band is a vibration characteristic related to defects, boundaries and disordered carbon arrangement in the material. The G band belongs to sp 2 The plane vibration mode of carbon atoms can be used as a quantitative indicator to evaluate the graphitization level of carbon-based materials. D / I G ) indicates sp 3 and sp 2 The ratio of carbon atoms reflects the degree of internal defects and disorder in the graphite carbon layer. Figure 2 It can be seen that FeS 0.1 -BC and FeN0.1 -BC's I D / I G The values ​​are 1.17 and 1.20 respectively. This shows that the carbon graphitization degree of the two materials obtained by calcination is equivalent. Compared with the comparative example 1, the content of melamine in Examples 1 to 3 is increased from 0 to 20%, I D / I G The value of also increases, indicating that there are defects in the composite absorbing material, which is conducive to the induction of defect polarization, and defects can trigger polarization relaxation, resulting in an increase in dipole polarization loss. At the same time, polarization relaxation can enhance electron transfer and generate heat energy, consuming electromagnetic waves. In addition, defect sites can also capture carriers and destroy the balance of charge distribution, further affecting the polarization process and electromagnetic energy attenuation.

[0101] Experimental Example 2

[0102] XPS Characterization Analysis of Composite Absorbing Materials

[0103] The binding energy of the composite absorber obtained in Example 2, Example 5 and Comparative Example 1 was analyzed by X-ray photoelectron spectroscopy (XPS, Thermo Scientific K-Alpha, USA), and the C1s peak of 284.8 eV was used as the internal standard to ensure the accuracy and reliability of the chemical bond state determination. The results are as follows: Figure 3 shown.

[0104] Depend on Figure 3 It can be seen that the main characteristic peaks confirm the existence of C1s, Fe 2p, N 1s, S2p and O1s, indicating that the iron nanoparticles are attached to the carbon material, and the heteroatoms N and S are also successfully incorporated into the carbon material, indicating the successful preparation of the composite absorbing material.

[0105] Experimental Example 3

[0106] SEM and TEM characterization and analysis of composite absorbing materials

[0107] Field emission scanning electron microscopy (FESEM, CLARA GHM) was used to examine the 0.1 -BC) and Example 5 (FeS 0.1 The morphology of the composite absorber obtained by Example 2 (FeN-BC) was characterized by high-resolution transmission electron microscopy (HR-TEM, JEOL JEM-2100F). 0.1 -BC) were analyzed, and the results are shown in Figure 4 shown. Figure 4 (a) is a SEM image of the composite absorbing material obtained in Example 5. Figure 4 (b) is a SEM image of the composite absorbing material obtained in Example 2. Figure 4(c) is a TEM image of the composite absorbing material obtained in Example 2.

[0108] like Figure 4 Middle (a), Figure 4 As shown in (b), FeS 0.1 -BC and FeN 0.1 -BC all present a three-dimensional porous layered structure, and particle agglomeration can be observed on the surface. Figure 4 In (c), it is observed that the nearly spherical iron nanoparticles are firmly attached to the porous carbon, and the lattice spacing of the iron nanoparticles is shown, which is specifically 0.25nm and 0.2nm. These measurements correspond to the (311) plane of Fe3O4 and Fe 0 The (110) surface of FeN 0.1 The iron nanoparticles in BC are mainly composed of Fe 0 and Fe3O4, providing ferromagnetism for the composite absorbing material, thereby promoting impedance matching and enhancing magnetic loss capacity.

[0109] Experimental Example 4

[0110] Testing of the microwave absorption performance of composite microwave absorbing materials

[0111] Example 2 (FeN 0.1 -BC), Example 5 (FeS 0.1 The composite absorbing materials obtained in Example 1 (Fe-BC) and Comparative Example 1 (Fe-BC) were mixed with paraffin in a weight ratio of 1:4, and the mixture was pressed into concentric rings with an outer diameter of 7 mm and an inner diameter of 3 mm. The electromagnetic performance test was carried out, and the absorbing ability test was carried out on an N5230 vector network analyzer. The frequency range of the electromagnetic parameters tested was 2-18 GHz. The 2D and 3D reflection loss contour diagrams of the obtained composite absorbing materials are shown in FIG. Figure 5 shown.

[0112] Figure 5 (a) is the 2D reflection loss contour diagram of comparative example 1, Figure 5 (b) is a 3D reflection loss contour diagram of Comparative Example 1; Figure 5 (c) is a 2D reflection loss contour diagram of Example 2, Figure 5 (d) is a 3D reflection loss contour map of Example 2; Figure 5 (e) is a 2D reflection loss contour diagram of Example 5, Figure 5 (f) is the 3D reflection loss contour map of Example 5.

[0113] observe Figure 5 , when the thickness is 5mm, Fe-BC and FeS 0.1 -BC RL in 17.9GHz and 18GHz bands minThe two samples do not show good f in the 2-18 GHz range, compared with FeN 0.1 -BC lacks obvious microwave absorption performance. The reason is that the Fe nanoparticles in the carbon matrix are highly aggregated and the sulfur components evaporate at high temperatures. 0.1 -When the BC filling amount is 20wt%, the f at 1.5mm is 4.8GHz (13.2-18GHz), and the RL at 1.8mm is min It is -63.2dB (12.3GHz). 0.1 -BC has better absorption capacity than FeS 0.1 -BC.

[0114] When N is doped into Fe-BC materials, since N has a higher electronegativity than C atoms, it can attract surrounding electrons, resulting in a redistribution of charge between N and C atoms. This charge transfer increases the concentration of free electrons in the material, thereby improving its conductivity. In contrast, although S atoms also have a higher electronegativity, the difference with C atoms is not as obvious as N, resulting in a weaker regulatory effect of S doping on charge transfer and carrier concentration. In addition, N doping introduces more heterogeneous interfaces (such as NC and N-Fe interfaces) into Fe-BC materials. These interfaces produce interfacial polarization effects under microwave irradiation, enhancing the microwave absorption performance of the material. Although S doping also introduces heterogeneous interfaces, the electronegativity and atomic radius of N atoms are more conducive to the formation of an interface structure that is conducive to the polarization effect. N atoms in Fe-BC materials act as dipole centers and undergo dipole polarization under microwave action. In contrast, S atoms exhibit a relatively weak dipole polarization effect in Fe-BC. In addition, N doping helps to improve the structural stability of the material, enabling it to maintain good microwave absorption performance in harsh environments such as high temperature and high humidity.

[0115] Experimental Example 5

[0116] Test of the wave absorbing performance of the composite wave absorbing materials of Examples 1 to 3

[0117] The same experimental method as that of Experimental Example 3 was used to test the absorbing properties of the composite absorbing materials of Examples 1 to 3, and the results were as follows: Figure 6 2D and 3D reflection loss contour diagrams of Examples 1 to 3 are shown.

[0118] Figure 6 (a) is a 2D reflection loss contour diagram of Example 1, Figure 6 (b) is a 3D reflection loss contour map of Example 1; Figure 6 (c) is a 2D reflection loss contour diagram of Example 2, Figure 6(d) is a 3D reflection loss contour map of Example 2; Figure 6 (e) is a 2D reflection loss contour diagram of Example 3, Figure 6 (f) is the 3D reflection loss contour map of Example 3.

[0119] observe Figure 6 It can be seen that FeN 0.05 - RL of BC at 4.8mm min The f at 2.6 mm is -22.1 dB (17.3 GHz), and the f at 2.6 mm is 1.9 GHz (10.03-11.93 GHz). 0.2 -BC has the best RL of -20.2dB (16.3GHz) at 5mm, while f at 2.6mm is only 0.7GHz (10.32-11.02GHz). 0.1 -BC f is 4.8GHz (13.2-18GHz) at 1.5mm, RL at 1.8mm min It is -63.2dB (12.3GHz). This shows that the greater the amount of heteroatom doping, the better the performance is, that is, there is an optimal doping level. Insufficient doping will not significantly change the electromagnetic properties of biochar, while excessive doping will destroy the material structure, excessively increase the conductivity, or disrupt the polarization mechanism, and ultimately reduce its attenuation effect on microwaves. As the doping level increases, the electromagnetic properties of biochar usually undergo a process of initial improvement followed by degradation. This is because moderate doping can optimize the electronic structure and polarization mechanism of the material, while excessive doping will introduce too many defects and scattering centers, hindering electron transfer or reducing microwave scattering efficiency.

[0120] Experimental Example 6

[0121] The test method of Experimental Example 5 was used to obtain the absorbing properties of the composite absorbing material obtained in Example 2 at different thicknesses. Figure 7 As shown, Figure 7 : Reflection loss (RL) and frequency (f) of the composite material of Example 2 with different thicknesses.

[0122] observe Figure 6 and Figure 7 It can be seen that FeN 0.1 As a microwave absorbing material, -BC has the excellent properties of "thin thickness, low reflection and wide bandwidth".

[0123] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, ordinary technicians in the field should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A method for preparing a cherry pit-derived magnetic porous carbon-based composite absorbing material, characterized in that: The preparation method comprises: (1) dispersing FeCl3, cherry pit powder and heteroatom dopant in anhydrous ethanol under stirring, and continuing to stir until the ethanol is completely volatilized to obtain a solid mixture; (2) grinding the solid mixture to obtain a precursor mixture; (3) placing the precursor mixture in a tube furnace and calcining it in an inert gas atmosphere to obtain the composite absorbing material.

2. The method for preparing the cherry pit derived magnetic porous carbon-based composite absorbing material according to claim 1, characterized in that: The heteroatom dopant includes melamine or Na2S2O3·5H2O.

3. The method for preparing the cherry pit derived magnetic porous carbon-based composite absorbing material according to claim 1, characterized in that: The weight ratio of the cherry pit powder to the Fe atoms is 1:1, and the mass percentage of the heteroatom dopant in the composite wave absorbing material is 5-20%.

4. The method for preparing the cherry pit derived magnetic porous carbon-based composite absorbing material according to claim 1, characterized in that: The weight volume ratio of the cherry pit powder to the anhydrous ethanol is 2g:25-30mL.

5. The method for preparing the cherry pit derived magnetic porous carbon-based composite absorbing material according to claim 1, characterized in that: In step (1), the temperature during the preparation of the solid mixture is 60-65°C.

6. The method for preparing the cherry pit derived magnetic porous carbon-based composite absorbing material according to claim 1, characterized in that: The particle size of the precursor mixture is 80-100 meshes.

7. The method for preparing the cherry pit derived magnetic porous carbon-based composite absorbing material according to claim 1, characterized in that: The calcination process specifically includes: placing the precursor mixture in a tube furnace, heating it to 800°C at a heating rate of 5°C / min in an inert gas atmosphere, calcining it at 800°C for 6h, and then naturally cooling it to room temperature to obtain the composite absorbing material.

8. The method for preparing the cherry pit derived magnetic porous carbon-based composite absorbing material according to claim 1, characterized in that: The inert gas includes argon or nitrogen.

9. A cherry pit derived magnetic porous carbon-based composite absorbing material, characterized in that: The composite absorbing material is made by the method described in any one of claims 1-8.

10. An application of a cherry pit derived magnetic porous carbon-based composite absorbing material, characterized in that: The composite absorbing material is made by the method described in any one of claims 1 to 8, or is the composite absorbing material described in claim 9, and the composite absorbing material is applied in the field of microwave absorption.